Efektivitas Latihan Kaki terhadap Diameter Edema - Sheilla Manawan; Maria Elsye Rosa (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effectiveness of foot pump exercise on edema diameter in patients with leg edema. The research method used is a literature review. The results showed a significant decrease in pitting edema and edema diameter when doing leg exercises in patients with leg edema. In conclusion, leg exercises in flexion and extension in the edematous leg area combined with leg elevation decrease the edema diameter. Keywords: Fluid Overload, Leg Edema, Leg Pump Exercise